Korelasi Antara Perhatian Orang Tua Terhadap Kemampuan Membaca Al-Qur’an Siswa Madrasah Ibtida’iyah Negeri Bawu Jepara - Muhammad Mukhofifin; Fatimah Azzahra; Ahmad Saefudin (Jurnal Riset Madrasah Ibtidaiyah, 2022)
Factors that affect students' ability to read the Koran can certainly come from within and from outside, factors that come from outside students include attention from parents. Meanwhile, internal factors can be influenced by the willingness to learn from the students themselves. Students who have a high enthusiasm for learning can improve their ability to read the Koran, but this can be encouraged by the attention of parents in the form of providing learning support facilities, learning motivation, learning assistance, and so on. This study aims to determine the relationship between parental attention to the ability to read the Koran of students at Madrasah Ibtida'iyah Negeri Bawu Jepara. This type of research is a field research with a quantitative approach. Data collection techniques used are questionnaires, interviews, and documentation. The population in this study were all fourth grade students, totaling 167 students. With a sample of 50 students using stratified sampling technique. The results of this study from calculations using product moment correlation found that the rcount value of 0.907 was greater than the rtable value of 0.279 at a significance of 5%. This shows that parental attention as a variable (x) has a significant relationship with students' ability to read Al-Quran as a variable (y). The greater the attention of parents, the higher the students' ability to read Al-Quran, and vice versa.